Level I Nodal Positivity as a Factor for Involvement of the Submandibular Gland in Oral Cavity Carcinoma: A Case Series Report - Pasha, Hamdan Ahmed; Dhanani, Rahim; Ghaloo, Shayan Khalid; Ghias, Kulsoom; Khan, Mumtaz Jamshed (International Archives of Otorhinolaryngology, 2020)
Introduction The routine practice of neck dissection in the surgical management of oral carcinoma has evolved into a more functionally conservative approach. Over time, the rationale for removal of the submandibular gland has been questioned. Routine extirpation of the submandibular gland can aggravate the xerostomia experienced by many patients, significantly affecting their quality of life.Objective The objective of the present study was to determine the incidence of submandibular gland metastases in oral cavity carcinoma and to identify possible factors that may affect their involvement.Methods A total of 149 cases of oral carcinoma presenting at a private tertiary care hospital in Karachi, Pakistan, over the course of 1 year were reviewed retrospectively.Results Histopathological data showed that the submandibular gland was involved in 7 (4.7%) cases. Involvement of level I lymph nodes was found in all of the cases. Direct extension of primary tumor was noted in two cases when the primary tumor was in the floor of the mouth.Conclusion The results suggest that preservation of the submandibular gland during neck dissection for oral carcinoma can be practiced safely when there is no evidence of direct extension of the primary tumor toward the submandibular gland or when there is no clinical or radiological evidence of neck disease in level I. Presence of pathological lymph nodes in level I requires caution when contemplating preservation of the submandibular gland.
Keywords: oral cavity; carcinoma; submandibular gland; xerostomia; neck dissection